Digital Health Transformation, Smart Ageing, and Managing Disability: 20th International Conference, ICOST 2023, Wonju, South Korea, July 7–8, 2023, Proceedings - Jongbae, Kim; Mokhtari, Mounir; Aloulou, Hamdi; Abdulrazak, Bessam; Seungbok, Lee (Lecture Notes in Computer Science, 2023)
This open access book constitutes the refereed proceedings of the 20th International Conference on Digital Health Transformation and Smart Ageing, ICOST 2023, held in Wonju, South Korea, during July 7–8, 2023. The 18 full papers and 16 short papers included in this book were carefully reviewed and selected from 41 submissions. They were organized in topical sections as follows: IoT and AI Solutions for E-health, Biomedical and Health Informatics, Wellbeing Technologies, Short Contributions: Medical Systems and E-health Solutions and Short Contributions: Wellbeing Technologies.